(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Mobile phones have become an integral part of everyone’s life. Radiofrequency electromagnetic waves emitted from mobile phone interact with biological system and lead to increase in reactive oxygen species (ROS) which alters several biochemical processes. Therefore, to investigate the harmful effect of the radiations generated from 3G mobile phones, we analyzed the changes in hematological parameters of male Wistar rats. In present study, exposure of 3G mobile phone radiation was given to ten weeks old male Wistar rats (n=8) for 2 hoursday. The exposure was continued for duration of 45 days in specially designed exposure set up. On completion of exposure time period, hematological and immunological parameters of blood were performed. A significant change in WBC and lymphocytes counts was found. Therefore this may be concluded that mobile phone radiation effect the hematological parameters.